Pharmaceutical development of phytosomes of Carica papaya leaf extract using the quality by design (QbD) approach - Rana, Rinu; Ashawat, Mahendra Singh (Journal of Neonatal Surgery, 2025)
The aim of the research work is to develop phytosomes of Carica papaya leaf extract (CPLE) and optimize its formulation with help of Quality by Design (QbD) method. The study involved the preparation of hydroalcoholic extract of fresh leaves. The extract underwent UV-Visible spectrophotometric analysis establishing a standard calibration curve. Phytosomes were formulated using a rotary evaporator method, with varying concentrations of phosphatidylcholine and cholesterol, optimized through a Full Factorial Design and Response Surface Methodology and characterized. The optimization led to the identification of formulation F5, which contained 2% phosphatidylcholine and 0.2% cholesterol, exhibiting the highest entrapment efficiency. Particle sizes ranged from 265 to 322 nm, while zeta potential values were between -21 and -40. Scanning and Transmission Electron Microscopy confirmed the spherical shape and uniform size distribution of the phytosomes. Stability studies showed no significant changes in particle size, zeta potential, or entrapment efficiency over 180 days. The study successfully developed a phytosomal formulation from Carica papaya leaf extract, optimized for particle size and entrapment efficiency. The results highlight the potential of the formulated phytosomes as a stable and effective delivery system, providing a promising avenue for future therapeutic applications